INTERNALISASI NILAI-NILAI MARDHATILLAH DALAM PEMBENTUKAN KARAKTER SISWA DI SD IT ALAM GARUT - Sapitri, Wina; Mulyani, Yani; Rofi Fahmi, Dede; Assalam, Sunan Hanif Ihsan; Hambali, Adang; Basri, Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to explore the process of internalizing mardhatillah values in shaping students' character at SD IT Alam Garut. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving school principals, teachers, students, and parents. The findings reveal that the internalization process takes place through exemplary behavior by teachers, consistent religious routines, integration of values into the curriculum, and the establishment of a value-based school culture. Students exhibit positive character traits such as honesty, responsibility, discipline, and empathy, which are rooted in spiritual awareness. However, challenges arise in sustaining these values outside the school due to limited parental involvement and inconsistent reinforcement at home. The school leadership plays a crucial role in ensuring that the vision of mardhatillah remains the foundation of educational programs and institutional policies. Overall, the internalization of mardhatillah values at SD IT Alam Garut contributes effectively to the development of students’ character, although it requires stronger synergy between school and family to maintain consistency in students’ moral behavior across contexts. Keywords: mardhatillah values, character education, internalization;